The capitalist state and the construction of civil society : public funding and the regulation of popular education in Sweden, 1870-1991 /: public funding and the regulation of popular education in Sweden, 1870-1991. ([2017]) - Berg, Anne, 1981-; Edquist, Samuel
No abstract available